DETERMINATION OF SERO-PREVALENCE AND ASSOCIATED RISK FACTORS OF BOVINE VIRAL DIARRHEA VIRUS (BVDV) IN BOVINE POPULATION FROM SOUTHERN PUNJAB, PAKISTAN - A. Raheem; A. Ahmad1; M. Rabbani; A. Ghafoor; A.A. Ajnum; M. Avais; Qurat-ul-Ain; R. M. Ramiz1and H. Ur-Rehman (Journal of Animal and Plant Sciences, 2020)
Bovine viral diarrhea (BVD) is an infectious disease of cattle and buffaloes, caused by bovine viral diarrhea virus (BVDV) and is distributed worldwide. BVDV leads to considerable economic losses and causes productive and reproductive problems. In this study, sero-prevalence and risk factors associated with BVDV in dairy animals of southern Punjab, Pakistan were determined. Three main Divisions of Southern Punjab including Bahawalpur, Multan and Dera Ghazi khan having a high density of animals, were selected for sampling. The farms having some reproductive problems were targeted for the collection of samples. Sample size was calculated by using Thrushfield formula assuming 50% prevalence of BVDV. In this study, a total of 719 samples from cattle (n=651) and buffaloes (n=68) were taken from 40 different dairy herds and processed for the presence of antibodies against BVDV through antibody capture ELISA. Out of all processed samples, overall, 18.77% positivity against BVDV was observed. Out of cattle samples (n=651), 19.81% (129/651) animals showed seroconversion against BVDV and 8.82% (6/68) in buffaloes, respectively. In this study, various risk factors associated with BVD such as entry of new animals, biosecurity, herd size and abortion were evaluated using odds ratio. It was interesting to note that only the entry of newly purchased animals showed a positive association with BVDV. The study concluded that BVDV is circulating in dairy animals of southern Punjab, Pakistan, and there is a need to test the status of newly purchased animals for BVDV before their entry in the farms.
Keywords: Bovine viral diarrhea virus; BVDV; Sero-prevalence; Risk factors; Southern Punjab